Acaricidal and anthelmintic action of ethanolic extract and essential oil of Achyrocline satureioides - Fantatto, Rafaela Regina [UNESP]; Chagas, Ana Carolina de Souza; Gainza, Yousmel Alemán [UNESP]; Politi, Flávio Augusto Sanches [UNESP]; Mesquita, Leonardo Mendes de Souza [UNESP]; Vilegas, Wagner [UNESP]; Bizzo, Humberto Ribeiro; Montanari Junior, Ílio; Pietro, Rosemeire Cristina Linhari Rodrigues [UNESP] (Elsevier, 2022)
Although Brazilian livestock is considered one of the most productive in the world, the losses caused by parasites still greatly limit these activities and its incorrect control through traditional synthetic chemicals has caused problems such as parasitic resistance. The present study evaluated the anthelmintic and acaricidal action of ethanolic extract (EE) and essential oil (OE) obtained from Achyrocline satureioides inflorescences against an endo and an ectoparasite of great importance in sheep and cattle. The action against Haemonchus contortus was evaluated by the Larval Development Test (LDT) and the Egg Hatching Test (EHT), while the acaricidal potential against Rhipicephalus (Boophilus) microplus was evaluated by the Adult Immersion Test (AIT) and Larval Package Test (LPT). Chemical analyzes were performed by liquid chromatography coupled to mass of spectrometry (LC-MS) and gas chromatography coupled to mass spectrometry (GC-MS) in order to evaluate the chemical composition of EE and EO, respectively. Luteolin (m/z 285), quercetin (m/z 301) and methyl quercetin (m/z 315) were the major compounds detected in the A. satureioides EE, while 41 compounds were identified in EO. Among them, the major compounds were caryophyllene oxide (15.4%), limonene (10.9%), trans-calamenene + δ-cadinene (8.0%), (E)-caryophyllene (5.5%), spathulenol (5.1%) and α-pinene (4.5%). Against H. contortus, by EHT, the EE and EO showed LC50 of 83.14 mg mL−1 and 10.42 mg mL−1, respectively. In LDT, LC50 were 0.16 mg mL−1 and 0.42 mg mL−1, respectively by EE and EO. In the AIT assay for R. (B.) microplus tick LC50 obtained for EE and EO were 76.43 mg mL−1 and 114.35 mg mL−1, respectively. EE at 100 mg mL−1 completely inhibited egg laying, while the EO at 50 mg mL−1 completely inhibited larval hatching. No significant larvicidal effect was observed in LPT for both extracts. The EE and EO presented a high efficacy at low concentrations in the inhibition of egg hatching and larval development of H. contortus. Although both extracts did not show consistent larvicidal action, the results were significant in inhibiting the oviposition of R. (B.) microplus engorged females.
Keywords: Achyrocline satureioides; Crude extract; Essential oil; Haemonchus contortus; Rhipicephalus (Boophilus) microplus